A new species of Lepidium (Brassicaceae) in the Cook Islands - Sykes, W. R. (Phytotaxa, 2014)
Lepidium makateanum is a small, erect, densely bushy shrublet confined to areas of makatea (raised coral) on Miti‘aro in the Ngaputoru Group north-east of Rarotonga.  It is closely related to L. bidentatum, a common coastal species throughout East Polynesia.  On some other islands of East Polynesia, other taxa are also said to be closely related to L. bidentatum, but none represent the Miti‘aro plant.